2012
DOI: 10.1016/j.lungcan.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Higher expression of EphA2 and ephrin-A1 is related to favorable clinicopathological features in pathological stage I non-small cell lung carcinoma

Abstract: Higher expression of EphA2 and ephrin-A1 was more related to the female sex, reduced smoking status, adenocarcinoma, well differentiated carcinomas, p-stage IA, and EGFR gene mutations. Higher EphA2 mRNA expression in p-stage I NSCLC patients was positively related to improved prognoses. These results may reflect a tumor suppressive role for the EphA2/ephrin-A1 system in a population of patients restricted to p-stage I NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…However, ephrin-A1 was not associated with any of the clinicopathological parameters apart from histological type. Interestingly, we found that adenocarcinomas had a higher percentage of S100A4 and ephrin-A1 positivity compared to squamous and large cell tumors, and this finding is in keeping with that of previous studies on S100A4 [7-9] and ephrin-A1 [25]. The histological subclasses of NSCLC differ not only in their presentation in different regions of the lung and in outcome [26], but also in molecular characteristics and thereby in response to targeted therapies [27].…”
Section: Discussionsupporting
confidence: 92%
“…However, ephrin-A1 was not associated with any of the clinicopathological parameters apart from histological type. Interestingly, we found that adenocarcinomas had a higher percentage of S100A4 and ephrin-A1 positivity compared to squamous and large cell tumors, and this finding is in keeping with that of previous studies on S100A4 [7-9] and ephrin-A1 [25]. The histological subclasses of NSCLC differ not only in their presentation in different regions of the lung and in outcome [26], but also in molecular characteristics and thereby in response to targeted therapies [27].…”
Section: Discussionsupporting
confidence: 92%
“…Contrary, in the present study, ccRCC patients with a high EFNA1 protein expression had frequently a lower tumor stage (p = 0.004). We did not find any link between EFNA1 protein expression and patient outcome, which is supported by other studies in patients with gastric [17] and lung [27] cancer. However, a high protein expression of EFNA1 was linked to poor survival in patients with vulvar [12] and cervical [11] carcinomas.…”
Section: Discussionsupporting
confidence: 90%
“…Together, these observations suggest that, whereas tumor-specific deletion of EphA2 promotes tumorigenesis, the contribution of EphA2 from tumor stroma and endothelial cells might be important for tumor development. Some human lung adenocarcinoma patients show increased expression of EphA2, and it is correlated with poor prognosis (39), whereas coexpression of high EphA2 and EfnA1 has favorable survival (40). Interestingly, TCGA data analysis revealed that EphA2 and EfnA1 alterations occur independently, and it is intriguing to hypothesize that tumors with EphA2 and EfnA1 coexpression might be negatively selected in the early stages of tumor development.…”
Section: Discussionmentioning
confidence: 99%